43=(X)+(5x+1)

Simple and best practice solution for 43=(X)+(5x+1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 43=(X)+(5x+1) equation:



43=(X)+(5X+1)
We move all terms to the left:
43-((X)+(5X+1))=0
We calculate terms in parentheses: -(X+(5X+1)), so:
X+(5X+1)
We get rid of parentheses
X+5X+1
We add all the numbers together, and all the variables
6X+1
Back to the equation:
-(6X+1)
We get rid of parentheses
-6X-1+43=0
We add all the numbers together, and all the variables
-6X+42=0
We move all terms containing X to the left, all other terms to the right
-6X=-42
X=-42/-6
X=+7

See similar equations:

| x+4x+5x=119+3x | | 175m-125m+48500=50750-200m | | 35-4x^2=-14 | | 31+33+4b=180 | | 3/2=x/400 | | 4x/8+2=3 | | 3m-16=9m+8 | | 98+-4x=-11x | | 48/u=(-3) | | 19n=361 | | 0.6x-5+0.1x=7 | | z-44+z=z+35 | | 22h-40=-72 | | 0.5(10x+15)–1.5=2x+6+3x | | c-32+c-45=c | | n-7/6=-2 | | -4(2-3n)=-44 | | n/14=7 | | 4/3•x=56 | | 32/8=28x | | 47/8n=-4/7 | | n-6÷3=-4 | | 1500=1x19.85 | | x+9/5=-6 | | n*5=215 | | X+4(3-3x)=56 | | 6-7=5x-10x-4 | | (-3x+30)+(5x-10)=3x+16 | | 6x – 1 = 5 | | |1-x|=-5 | | 3x+9=–2x+19+x | | n/7=44 |

Equations solver categories